Educación y Formación de la Ciudadanía: una visión desde la configuración socio-humanéstica-sostenible - Márquez Ramírez, Ysrael O. (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This document has as a general purpose, to exam the epistemic gnoseologic aspects related to the theme of citizenship education and civic education. It is also an interpretation-hermeneutic approach which conceived the notion of education as the key in formation of citizens at the context of the processes of globalization phenomenon and the global redefinition of society in postmodern times. In this sense, there is a position in terms of setting a sustainable socio-humanistic which seeks to interpret the trends and educational events and training with special emphasis on the specific regional, Latin American and Caribbean countries. Since these pre-orientation lines, the basis of theoretical epistemic plotted a variety of lines of thoughts that fit the argument in the current debate about the “human dimension” and complexity of contemporary social thought. A gnoseo contextual frame open to reflection and the discursive construction binding on the matter of interest, at the same time, taking into account the points made by authors like Adela Cortina, Edgar Morin, Manuel Castells, Gabriel Parra, Gabriel Ugas and Magda Cejas , among others. In short, this network of thoughts that are hyperlinked on propositional pages intends to engage roads to those renowned imaginaries towards education and training of citizens from the cultural-historical diversity and plurality as well as reassess the human condition in multidimensional terms,holistic and integrative
Keywords: Education; Citizenship; Learning; Preparation; Society; Sustainability